Benetti, C. Valeur et Répartition. Presses Universitaires de Grenoble-F. Maspero, 1974; BENETTI, C., C. BERTHOMIEU, J. CARTELIER. Economie Classique, Econo-mie Vulgaire, Presses Univ. de Grenoble-F. Maspero, 1975.; CARTELIER, J. Surproduit et Reproduction, Presses Univ. de Grenoble-F. Maspero, 1976. - Nadal Egea, Alejandro (El Colegio de México A.C., 1980)
BENETTI, C. Valeur et Répartition, Presses Universitaires de Grenoble-F. Maspero, 1974. BENETTI, C, C. BERTHOMIEU, J. CARTELIER. Economie Classique, Economie Vulgaire, Presses Univ. de Grenoble-F. Maspero, 1975. CARTELIER, J. Surproduit et Reproduction, Presses Univ. de Grenoble-F. Maspero, 1976.